New mechanisms of bacterial arsenic resistance - Hung-Chi Yang; Barry P. Rosen (Biomedical Journal, 2016)
Arsenic is the most pervasive environmental substance and is classified by the International Agency for Research on Cancer as a Group 1 human carcinogen. Nearly every organism has resistance pathways for inorganic arsenic, and in bacteria, their genes are found in arsenic resistance (ars) operons. Recently, a parallel pathway for organic arsenicals has been identified. The ars genes responsible for the organoarsenical detoxification includes arsM, which encodes an As(III) S-adenosylmethionine methyltransferase, arsI, which encodes a C–As bond lyase, and arsH, which encodes a methylarsenite oxidase. The identification and properties of arsM, arsI and arsH are described in this review.